2021
DOI: 10.3390/children8090787
|View full text |Cite
|
Sign up to set email alerts
|

Test of Motor Proficiency Second Edition (BOT-2) Short Form: A Systematic Review of Studies Conducted in Healthy Children

Abstract: Motor skill competence of children is one of the important predictors of health because if a child is physically active during early childhood, the possibility of occurrence of many chronic diseases in adulthood will be reduced. The aim of this study was to systematically review the studies conducted in healthy children using the shorter form of the Bruininks-Oseretsky (BOT-2) and to determine the applicability in cross-sectional studies and pre-post designs. The search and analysis of the studies were done in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 90 publications
0
11
0
1
Order By: Relevance
“…Modern technologies (TV, tablet, smartphone, etc.) have a negative effect on motor competence and visual perception, fine motor precision and integration, manual dexterity, and strength 32 . Ling et al 40 have shown that the children who spent more time with modern technologies have poor performance on these tasks compared with children who spent less time with these tools.…”
Section: Discussionmentioning
confidence: 99%
“…Modern technologies (TV, tablet, smartphone, etc.) have a negative effect on motor competence and visual perception, fine motor precision and integration, manual dexterity, and strength 32 . Ling et al 40 have shown that the children who spent more time with modern technologies have poor performance on these tasks compared with children who spent less time with these tools.…”
Section: Discussionmentioning
confidence: 99%
“…The children are aged between 4 and 21 ( 26 , 27 ). The test is available in two forms, complete form (CF) and short form (SF) ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…This assessment is an additional burden for a child and even their parents. Therefore, many experts call for greater use of BOT-2 SF, whose advantage is a shorter administration time of 15 to 20 min ( 28 , 31 ). BOT-2 CF and BOT-2 SF have high reliability (0.9–0.97), and there is a strong correlation between these two test forms ( r = 0.80–0.87) ( 29 32 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations